Rose sees red - Castellucci, Cecil 1969- (Scholastic Press, 2010)
In the 1980s, two teenaged ballet dancers--one American, one Russian--spend an unforgettable night in New York City, forming a lasting friendship despite their cultural and political differences
Keywords: Geschichte 1900-2000; Ballet dancing / Fiction; Friendship / Fiction; Russians / New York (State) / New York / Fiction; Ballet dancing / Juvenile fiction; Friendship / Juvenile fiction; Russians / New York (State) / New York / Juvenile fiction; Geschichte; New York (N.Y.) / History / 20th century / Fiction; New York (N.Y.) / History / 20th century / Juvenile fiction